About the Connection Concerning the Processes of Transformations in Asia in the Second Part of the XIXc.- First Part of the XXc. And the Asian Economical Crisis in the end of 1990s (Mongolian Journal of International Affairs, 2014)
No abstract available The Mongolian Journal of International Affairs; Number 6, 1999, Pages 42-49